Research on the Tendency Relationship between Individual Stock and Stock Index - Jiao, Xiangyue; Liu, Songyang; Wang, Zixuan (BCP Business & Management, 2022)
This paper mainly centers on exploring the tendency relationship between individual stock and stock index using CAPM method. The research chooses the stock of Apple Inc. as an individual stock and S&P 500 as the stock index. Then CAPM is used to tests indicating that this model does not fit the rate of return on Apple very well. Therefore, this paper explores the possible reasons behind the phenomenon and refers to some constructive improvements in the evaluation of expected rate of return on individual stocks under the influence of the stock index. One reason is probably that AAPL is so powerful a corporation that it is extremely immune to anomalous volatility of the stock market, which implies that unsystematic risk dominates the trend of stock of Apple Inc. Therefore, this paper suggests that CAPM model should only be applied when the target company is a small-sized or medium-sized one that is prone to the fluctuation of the stock market.